An examination of the response of the Cape Mental Health Society to the mental health needs of blacks in the Western Cape - Mangwana, Thobeka Cikizwa (1989)
Includes bibliography.This study examined the response of the Cape Mental Health Society to the mental health problems of Blacks in the Western Cape. This response has been examined against the organisational and the community contexts in which such services are provided. Environmental constraints which surround service provision were examined at macro- and micro-level. The macro-level covered the unfavourable political, social and economic aspects as experienced by both the organisation and its clientele. The micro-level covered those aspects which impinge on service delivery but are within the scope of the organisation. It is agreed that these aspects affect the nature of the response of the organisation to mental health needs of blacks negatively. The study emphasizes the need to define mental health within the South African context from a psychiatric and socio-political perspective as such a definition allows for appropriate service provision. Data was collected from primary and secondary sources. Interviewing was used as a technique for collecting primary data. Structured and unstructured interviews were carried out with people from various disciplines, community members, and present and prospective service consumers. The exploratory-descriptive approach was used. The problems and needs of clients were quantified in terms of the organisation's waiting lists and other criteria. Services rendered by the Society were quantified in terms of clients being served and the number of projects and programmes undertaken to meet different mental health needs. Ideas have been developed about mental health services amongst the black communities and their cultural perception of mental health needs. The findings emphasize inadequacy of the response of the Cape Mental Health Society to mental health needs of blacks. The present facilities are insufficient and inappropriate to mental health needs of blacks. They are characterised by inaccessibility, inefficiency and ineffectiveness where they do exist. A marked inequality in the provision of services to the two population groups, that is, Coloureds and Blacks, has been identified. A framework for developing mental health services for blacks in the Western Cape has been recommended. This framework proposed various steps which can be taken in such development